Characterization of phenylalanine hydroxylase alleles in untreated phenylketonuria patients from Victoria, Australia: origin of alleles and haplotypes. - Ramus, S J (1995)
Mutations in the phenylalanine hydroxylase (PAH) gene were identified in a group of untreated phenylketonuria patients from Victoria, Australia. Ninety-eight percent of the alleles were identified, and a total of 26 different mutations were detected on 83 independent chromosomes. The three most prevalent mutations--R408W, I65T, and IVS12nt1--together accounted for 54% of the alleles. A number of alleles were demonstrated, by genealogical studies, to be of Irish or Scottish origin, including a newly described mutation 1197/1198 del A. The distribution and relative frequencies of the more common alleles in this population parallel observed frequencies in the British Isles and are consistent with the known history of Caucasian settlement of this region of Australia. We have analyzed the haplotype and polymorphic short tandem-repeat allele of the mutant chromosomes and describe a number of new associations.